2016
DOI: 10.1007/s40265-015-0523-6
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Therapy for Idiopathic Pulmonary Fibrosis: Where To Now?

Abstract: Idiopathic pulmonary fibrosis (IPF) is an aging-associated recalcitrant lung disease with historically limited therapeutic options. The recent approval of two drugs, pirfenidone and nintedanib, by the United States Food and Drug Administration (FDA) in 2014 has heralded a new era in its management. Both drugs demonstrated efficacy in Phase III clinical trials by retarding the rate of progression of IPF; neither drug appears to be able to completely arrest disease progression. Advances in the understanding of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 122 publications
(110 reference statements)
0
39
0
Order By: Relevance
“…It is also possible that metformin exerts antifibrotic properties by ameliorating impaired autophagy (by activating AMPK, which in turn leads to enhanced autophagy and metabolic reprogramming, both of which have potential benefit in the context of aging-associated fibrosis) [27,36,37], and as some studies have linked IPF with impaired autophagic processes [38,39], we might expect metformin to have an effect on IPF outcomes. However, further research is needed to determine the link between autophagy and the molecular mechanisms of fibrogenesis in IPF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that metformin exerts antifibrotic properties by ameliorating impaired autophagy (by activating AMPK, which in turn leads to enhanced autophagy and metabolic reprogramming, both of which have potential benefit in the context of aging-associated fibrosis) [27,36,37], and as some studies have linked IPF with impaired autophagic processes [38,39], we might expect metformin to have an effect on IPF outcomes. However, further research is needed to determine the link between autophagy and the molecular mechanisms of fibrogenesis in IPF.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies have suggested that metformin has antifibrotic and anti-inflammatory effects [23][24][25]. Metformin has been found to attenuate lung fibrosis by inhibiting transforming growth factor-beta (TGF-β) via adenosine monophosphate-activated protein kinase (AMPK) activation [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…The discreet targets of Pirfenidone still remain unclear, yet it shows efficacy in delaying disease progression (16). Due to the heterogeneity of this disease, multiple targets in the fibrotic pathway lay open for potential intervention (17). …”
mentioning
confidence: 99%
“…Although affecting fewer people than IPF per se, similar pathological changes are seen in a minority of adult cancer survivors exposed to lung irradiation as part of their treatment, described as RIPF [5]; childhood lung cancer survivors also show a four-fold increased risk of developing pulmonary fibrosis after radiation treatment [6]. Currently, there are no approved treatment options for patients with RIPF, although regimens for IPF, such as Pirfenidone and Nimatinib, slow the progression of the disease [3, 7]. Efforts to halt or reverse the progression of pulmonary fibrotic disease have, to date, ended in failure.…”
Section: Introductionmentioning
confidence: 99%